Occipitocervical Dissociation in Three Siblings: A Pediatric Case Report and Review of the Literature - Glaun, Gabriel D. (J Am Acad Orthop Surg Glob Res Rev, 2018)
This report includes three cases of occipitocervical (OC) dissociation in three siblings involved in a single, head-on, motor vehicle accident. The oldest sibling, a 9-year-old girl, required surgical fixation. The second sibling, a 6-year-old boy, was treated nonsurgically with a neck brace. The youngest sibling, a 5-year-old boy, sustained a fatal OC dissociation. CT and MRI findings are used to assess the reliability of the currently recommended diagnostic modalities for OC dissociation. The literature review focuses on the diagnosis of OC dissociation via CT measurements and proposed treatment recommendations using CT and MRI classification systems. In the 9-year-old girl, the mean atlanto-occipital joint width, the interspinous ratio, and space available for cord measurements indicated OC dissociation. However, on MRI evaluation, OC dissociation was observed in both living siblings and severe ligamentous injury was noted in the girl. The proposed CT measuring techniques for the diagnosis of OC dissociation were inconsistent in our cases. In the setting of clinically suspected OC dissociation with normal CT measurements, we recommend obtaining a cervical spine MRI to properly assess the extent of ligamentous injury.